PENGARUHRETURN ON ASSETS (ROA), CAPITAL ADEQUACY RATIO (CAR), UKURAN BANK (BANK SIZE), LOAN DEPOSIT RATIO (LDR) DAN INFLASI TERHADAP NON PERFORMING LOAN (NPL) (Studi pada Perusahaan Perbankan di BEI Tahun 2013-2015) - Raditya Teddy Wicaksono, 13.05.51.0080 (Students' Journal of Economic and Management, 2017)
This study examines the effect of return on assets (ROA), capital adequacy ratio (CAR), bank size (BANK SIZE), loan deposit ratio (LDR), and inflation to non performing loan (NPL). The method used in this research is descriptive method that is quantitative. Sample technique using purposive sampling technique with research period year 2013 - 2015. The result of research show there is significant and negative influence between ROA to Non Performing Loan (NPL), there is no significant influence between CAR to Non Performing Loan (NPL) Which is significant and positive between Bank Size against Non Performing Loan (NPL), there is no significant influence between LDR to Non Performing Loan (NPL), and there is no significant influence and between Inflation to Non Performing Loan (NPL). Keywords: Return On Assets, Capital Adequacy Ratio, Bank Size, Loan to Deposit Ratio and Inflation to Non Performing Loan.